Engineering properties and fracture behaviour of high volume palm oil fuel ash based fibre reinforced geopolymer concrete. (15th May 2016) - Bashar, Iftekhair Ibnul; Alengaram, U. Johnson; Jumaat, Mohd Zamin; Islam, Azizul; Santhi, Helen; Sharmin, Afia
Highlights: High volume POFA (90%) was used in development of geopolymer concrete. Aspect ratio of steel fibre had significant effect on tensile properties. Tensile properties due to steel fibres are more significant in OPSGC than NWGC. Bonding between matrix and aggregate influenced tensile and fracture properties. Abstract: This article reports investigation carried out using high volume palm oil fuel ash (POFA-90%) based geopolymer concrete using oil palm shell (OPS) as coarse aggregate. The tensile and fracture properties of OPS based lightweight geopolymer concrete (OPSGC) with the addition of steel fibres (SF) of two aspect ratios (AR80, AR65) and three volume fractions (0.25%, 0.50%, 0.75%) were investigated. The results were compared with that of normal weight geopolymer concrete (NWGC) with and without steel fibre of AR80 and AR65 (0.50% volume fraction). The higher values of flexural and splitting tensile strengths of OPSGC could be attributed to stronger bond between the rougher surfaces of the crushed OPS and matrix. The addition of SF(AR80) produced higher splitting strength, flexural strength and total fracture energy of 5%, 6% and 50–80%, respectively compared to the corresponding values of SF(AR65) . The toughness and equivalent flexural strength ratio of OPSGC were found higher than the corresponding values of NWGC and this could be attributed to the ductility of OPS. The values of residual load and residual strength in two-deflection limits of L/600 and L/150 indicated the progressive failure, which reflected the ductility of the OPSGC with fibres.